Bio-inspired flow sensor from printed PEDOT:PSS micro-hairs. (4th February 2015) - Devaraj, Harish; Travas-Sejdic, Jadranka; Sharma, Rajnish; Aydemir, Nihan; Williams, David; Haemmerle, Enrico; Aw, Kean C
Abstract: This paper reports on the creation of a low-cost, disposable sensor for low flow velocities, constructed from extruded micro-sized 'hair' of conducting polymer PEDOT. These microstructures are inspired by hair strands found in many arthropods and chordates, which play a prime role in sensing air flows. The paper describes the fabrication techniques and the initial prototype testing results toward employing this sensing mechanism in applications requiring sensing of low flow rates such as a flow sensor in neonatal resuscitators. The fabricated 1000 μ m long, 6 μ m diameter micro-hairs mimic the bending movement of tactile hair strands to sense the velocity of air flow. The prototype sensor developed is a four-level direct digital-output sensor and is capable of detecting flow velocities of up to 0.97 m s −1 .